KONSISTENSI MENERAPKAN PERATURAN PERUSAHAAN DALAM PENGHITUNGAN KOMPENSASI PEKERJA PIMPINANYANG BEKERJA DI LAPANGAN OPERASI PADAPT.ABC - Firdaus Furywardhana (Arena Hukum, 2015)
AbstractExcess Hours of Work Compensation Formula Application (KKJK) for leaders who work in the field operations is the best solution to resolve the lack of consistent between rules and reality Excess Hours of Work Compensation (KKJK) payments for workers of the field operations. Formulation calculation of compensation excess working hours (KKJK) according agreed in LKS Bipartit with calculation 3.20% per day for work scheduled at 14:07 and 3.78% per day for the work scheduled at 16:12 forfield leader to be implemented consistently BeforeThe company will provide compensation 60% from the wages of a month to leaders who work in the Field Operations based on attendance, while the Fair Workers excess working hours counted as work overtime. This compensation is not included in the calculation as the wage component.Realization field leader compensation payments is given by 60% of the wages regardless of attendance in the operation field.Â AbstrakPenerapan Formula kompensasi kelebihan jam kerja (KKJK) bagi pekerja pimpinan di lapangan operasi merupakan solusi terbaik untuk menyelesaikan ketidak-konsisten antara aturan dan kenyataan pembayaran kompensasi kelebihan jam kerja (KKJK) bagi pekerja pimpinan di lapangan operasi.Formulasi perhitungan kompensasi kelebihan jam kerja (KKJK) sesuai disepakati dalam LKS Bipartit dengan perhitungan 3.20% per hari untuk jadwal kerja 14:7 dan 3.78% per hari untuk jadwal kerja 16:12 bagi pekerja pimpinan di lapangan operasi agar dilaksanakan secara konsisten. Sebelumnya Perusahaan akan memberikan kompensasi sebesar 60% dari Upah sebulan kepada Pekerja Pimpinan yang bekerja di Lapangan Operasi berdasarkan daftar kehadiran, Sedangkan kepada Pekerja Biasa kelebihan jam kerja dihitung sebagai kerja lembur. Kompensasi ini tidak termasuk dalam perhitungan sebagai komponen upah.Realiasasi pembayaran kompensasi pekerja pimpinan dilapangan diberikan sebesar 60% dari upah tanpa memperhitungkan jumlah kehadiran di lapangan operasi.